Adults With Special Educational Needs Participating in Interactive Learning Environments in Adult Education: Educational, Social, and Personal Improvements. A Case Study - Díez-Palomar, Javier; Ocampo Castillo, María del Socorro; Pascual, Ariadna Munté; Oliver, Esther (Frontiers in Psychology, 2021)
Previous scientific contributions show that interactive learning environments have contributed to promoting learners' learning and development, as interaction and dialogue are key components of learning. When it comes to students with special needs, increasing evidence has demonstrated learning improvements through interaction and dialogue. However, most research focuses on children's education, and there is less evidence of how these learning environments can promote inclusion in adult learners with SEN. This article is addressed to analyse a case study of an interactive learning environment shared by adults with and without special needs. This case shows several improvements identified by adult learners with special needs participating in this study. Based on a documental analysis and a qualitative study, this study analyses a context of participatory and dialogic adult education. From the analysis undertaken, the main results highlight some improvements identified in the lives of these adult women and men with SEN, covering educational improvements, increased feeling of social inclusion, and enhanced well-being.